2021
DOI: 10.1002/hlca.202100044
|View full text |Cite
|
Sign up to set email alerts
|

Strained Ruthenium Complexes Bearing Tridentate Guanidine‐Derived Ligands

Abstract: The dimer [{(η6‐p‐cymene)RuCl}2(μ‐Cl)2] (cymene=MeC6H4iPr) reacts with N,N′‐bis(p‐tolyl)‐N′′‐(2‐pyridinylmethyl)guanidine (H2L1) and N,N′‐bis(p‐tolyl)‐N′′‐(2‐diphenylphosphanoethyl)guanidine (H2L2), in the presence of NaSbF6, giving rise to chlorido compounds of formula [(η6‐p‐cymene)RuCl(H2L)][SbF6] (H2L=H2L1 (1), H2L2 (2)) in which the guanidine ligand adopts a κ2 chelate coordination mode. The related ligand (S)‐N,N′‐bis(p‐tolyl)‐N′′‐(1‐isopropyl, 2‐diphenylphosphano ethyl)guanidine (H2L3) affords mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Interestingly, in the search for new coordination modes, guanidines have been modified with other donor groups, such as phosphanes. In this way, ruthenium (II) (Figure 40) and osmium (II) complexes were obtained [145,146]. This type of multidentate ligand allows the preparation of the iridium and rhodium guanidinato complexes as 68, which behave as a frustrated Lewis pair (FLP) capable of reversibly activating polar bonds, such as those of water, and non-polar bonds, such as those of dihydrogen (Figure 41) [147,148].…”
Section: Transition Metal Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the search for new coordination modes, guanidines have been modified with other donor groups, such as phosphanes. In this way, ruthenium (II) (Figure 40) and osmium (II) complexes were obtained [145,146]. This type of multidentate ligand allows the preparation of the iridium and rhodium guanidinato complexes as 68, which behave as a frustrated Lewis pair (FLP) capable of reversibly activating polar bonds, such as those of water, and non-polar bonds, such as those of dihydrogen (Figure 41) [147,148].…”
Section: Transition Metal Complexesmentioning
confidence: 99%
“…Interestingly, in the search for new coordination modes, guanidines have been modified with other donor groups, such as phosphanes. In this way, ruthenium (II) (Figure 40) and osmium (II) complexes were obtained [145,146]. In contrast, less attention has been paid to osmium guanidinato complexes [137,144], although some examples were able to transform a wide variety of aldoximes selectively and catalytically into the corresponding nitriles (Figure 39).…”
Section: Transition Metal Complexesmentioning
confidence: 99%
“…Concomitantly, the complex features fused five- and four-membered metalacycles and the central nitrogen atom adopts a pyramidal sp 3 hybridization. A close inspection of the molecular structure of these complexes revealed that the structural parameters within the four-membered M–N–C–N metalacycle deviate significantly from those expected for an ideal hybridization of its atoms, therefore suggesting that this ring undergoes a high strain. Consequently, the metalacycle is prone to relieve this strain by means of the cleavage of the metal-iminic nitrogen bond under mild conditions, providing a vacant site at the metal and a lone electron pair on the involved nitrogen, that is, these compounds are masked TMFLPs.…”
Section: Introductionmentioning
confidence: 97%
“…During the last years, our research group has focused on the preparation and study of the reactivity of TMFLPs based on half-sandwich compounds bearing (η 5 -C 5 Me 5 )­Rh­(III) or ( η 6 - p -cymene)­M­(II) (M = Ru, Os) fragments. , A common and pivotal feature of these TMFLPs is that the included metal centers complete their coordination sphere, thanks to a monoanionic phosphano- or pyridinyl-guanidine ligand exhibiting a fac κ 3 coordination (Scheme A), thus ensuring the stabilization of the resulting complex. Concomitantly, the complex features fused five- and four-membered metalacycles and the central nitrogen atom adopts a pyramidal sp 3 hybridization.…”
Section: Introductionmentioning
confidence: 99%